Effect of mode of delivery on the level of zinc copper superoxide dismutase in umbilical cord blood - KHAWLA A.H. SHAMERAN MSC; MAY F.M AL-HABIB PHD; RAYAH S. BABAN PHD (International Journal of Pharma and Bio Sciences, 2016)
Normal pregnancy is associated with high metabolic demand and elevated requirements for tissue oxygen which results in increased oxidative stress as well as increased metabolic demands and deficiency of one or more of the trace elements (Zinc and Copper) which will lead to adverse maternal and perinatal outcomes. These two elements are essential for metalloproteinase enzymes such as superoxide dismutase. Babies were delivered either vaginally or through caesarean delivery depending on the circumstances surrounding the pregnancy from conception through labour. The current study was aimed to investigate umbilical cord blood levels of zinc, copper and superoxide dismutase in normal vaginal delivery and versus elective cesarean section. So, a case-control study was conducted in Baghdad Hospitals from January 2015 to May 2016. Sixty four pregnant women were involved to determined umbilical cord blood levels of zinc copper and superoxide dismutase in two mode of delivery; normal vaginal and elective cesarean section. A significant increase in the level of endogenous antioxidant enzyme superoxide dismutase (p <0.001) was found in cord blood of cesarean section versus normal vaginal delivery. Both zinc and copper shows a significant decrease in cord blood of cesarean section versus normal vaginal delivery (p<0.035 and 0.05 respectively). No significant correlation was found between trace elements and the antioxidant enzyme in cord blood of the two groups. In conclusion, as in caesarean section the antioxidant superoxide dismutase enzyme level is better than oxidative stress and was significantly elevated more than in normal vaginal delivery, so it can be concluded that elective caesarean section proves to be better mode of delivery than the normal vaginal delivery.